Analysis of Student Difficulties in Computer Programming - Abdul Baist; Aan Subhan Pamungkas (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Computer programming skills are required in mathematics computing courses. Most students have difficulty making computer programs. This study aims to identify the difficulties faced by students in making computer programs. This research is descriptive quantitative research. The subjects in this study are students of Mathematics Education Departement, Muhammadiyah University of Tangerang. Based on the results of data analysis, the conclusion is: (1) there are significant differences in multidimensional array material between high, medium and low group; (2) there is a significant difference in input / ouput command material between high, medium and low group; (3) there are significant differences about the difficulties experienced by students in understanding the basic concept of programming between high, medium and low groups; (4) there is a significant difference regarding the difficulties experienced by students in finding the fault of their own programs between high, medium and low groups; (5) there is no significant difference in situations that may assist students in programming for lab work in the high, medium and low groups; (6) there is no significant difference in situations that can assist students in programming to do alone tasks between high, medium and low groups; (7) there is no significant difference in the lack of examples shown when practice makes poor performance in programming between high, medium and low groups; (8) there is no significant difference in what makes poor performance in programming a less conducive atmosphere between high, medium and low groups.